The Corporation as a Protagonist in Global History, c. 1550-1750 - Pettigrew, William A.; Veevers, David; Pettigrew, William A.; Veevers, David (Brill, 2018)
In The Corporation as a Protagonist in Global History, William A. Pettigrew and David Veevers reinterpret the role of Europe$1 (Bs overseas corporations in early modern global history, uncovering their unique global sociology in the years 1550 to 1750. Readership: Academics and students interested in the history of trading corporations, European overseas enterprises, early modern global history, empire, trade and commerce, and business and economic historians.s
English
Keywords: General & world history; General & world history